Seismic behavior of special truss moment frame with double hollow structural sections as chord members. (15th January 2017) - Simasathien, Sanputt; Jiansinlapadamrong, Chatchai; Chao, Shih-Ho
Highlights: Special truss moment frames using double hollow structural sections for truss members. Double-HSSs minimize lateral torsional buckling and maximizing compactness in the flanges. Double-HSSs provide high rotational capacity of 0.09 rad before degradation occurs. Plastic hinge models are suggested for computer analysis and design of non-yielding members. Abstract: Research work carried out on steel special truss moment frames (STMFs) with double-angle sections as chord members during the 1990s led to the formulation of design code provisions. Further research results using double-channel specimens resulted in a modified equation for the expected vertical shear strength of the central special segments, Vne, and has been incorporated into the current AISC Seismic Provisions for Structural Steel Buildings . Double hollow structural sections (double-HSS) have the advantages of minimizing lateral torsional buckling and maximizing compactness in the flanges as compared to single HSS with the same flexural capacity. In this research, double-HSS members were proposed for the chord and web members of STMFs instead of double-angle, double-channel, or single-HSS. Double-HSS can effectively delay flange local buckling and enhance rotational ductility due to reduced width-to-thickness ratio ( b / t ) without increasing the wall thickness of the members. A full-scale STMF subassemblage with double-HSS as truss members was tested under large displacement reversals to simulate a severe earthquake ground motion. Testing results indicate that using double-HSS truss members is a viable alternative for STMFs in high seismic regions. Plastic hinge models are also suggested for computer analysis and design of non-yielding members outside of the special segments.